Why does nutrition deteriorate rapidly among children under 2 years of age? Using qualitative methods to understand community perspectives on complementary feeding practices in Bangladesh - Rasheed, S; Rukhsana, H; Hassan, N; Pachón, Helena; Islam, S.; Chowdhury, SBJ; Sanghvi, TG (2011)
Lay perceptions about complementary feeding differ substantially from international complementary feeding recommendations. A large proportion of children do not consume sufficient amounts of complementary foods to meet their energy and micronutrient needs. There was a gap in knowledge about appropriate complementary foods in terms of quality and quantity and strategies to convert family foods to make them suitable for children. Complementary feeding advice from family members, peers, and health workers, the importance given to feeding young children, and time spent by caregivers in feeding influenced the timing, frequency, types of food given, and ways in which complementary feeding occurred.